Identifikasi Cemaran Mikroba pada Jajanan Bakso di Kota Majene - Fitriani Fitriani; Said, Nur Saidah; Syah, Setiawan Putra (Pusat riset dan Inovasi Nasional, 2023)
High microbial contamination in food is an indicator of hygiene that determines the health of food for consumption. Meatballs are a very popular snack in Majene City. Apart from their delicious taste, meatballs also have a relatively cheap price, so they have always been a popular snack alternative. The high nutritional content in meatballs can be a medium for the growth of bacteria so meatballs can be carriers of disease. The aims of this study were to determine the total number of bacterial contaminants and identify the coliform in meatballs at Majene City. The study used a quantitative descriptive method with a sample of 10 traders. The test carried out was culturing bacteria on NA (Nutrient Agar) media to calculate the total number of microbes in meatballs using the Total Plate Count (TPC) method and EMBA (Eosin Methylene Blue Agar) media to determine the presence of coliform bacteria in the sample then continued with gram staining test. The results of the study showed that 3 samples were found on NA media which had microbial contamination levels exceeding the threshold specified in SNI (Indonesian National Standard) 3818:2014 where the highest amount allowed was 1 × 105 cfu/g. Samples that exceeded the threshold namely sample A was 1.33 × 106 cfu/g; sample C was 1.06 × 105 cfu/g; and sample G was 5.8 × 106 cfu/g. There were 5 samples that tested positive for coliform, namely samples A, B, C, D, and G